ADULT CARDIOTHORACIC SURGICAL SITE INFECTION REGISTRY; A PRELIMINARY ANALYSIS AND QUALITY IMPROVEMENT INITIATIVE - Zaidi, Sabeen Khurshid; Pervaiz, Farrah; Zameer, Ali Gohar; Chaudhry, Imtiaz Ahmed; Iqbal, Afsheen; Abbas, Safdar (Pakistan Armed Forces Medical Journal, 2015)
Objective: To establish the adult cardiothoracic surgical site infections registry to determine adult surgical site infection (SSI) rates and study impact of quality improvement initiatives on SSI rates.Methods: The adult Cardiothoracic SSI registry was developed and monthly SSI rates were monitored for both CABG and valvular heart surgeries inclusive of, chest and leg SSIs. Process improvements were instituted to control the increased SSI rate in October 2014 after a multidisciplinary brainstorming session.Results: A total number of 734 cardiac surgeries were carried out and the cumulative SSI rate was 1.7% (n=13) for this period of six months i.e. August 2014 to January 2015 and that for Chest infections was 1.3% (n=10) and for leg wound (harvest site) infections was 0.4% (n=3). There was an increase in SSI rate in October 2014 of 5% (n= 04). After process improvements the SSI rate declined to 1% in November 2014 and has remained less than or equal to 2% as of January 2015.Conclusion: A high SSI rate was investigated and multi-modal process improvements and infection control measures were implemented, leading to a decrease in SSI rate from 4% to 1%.